Phenomenon of trilingualism in a sanandresano migrant: case study (2018)
TABLE OF CONTENTS Introduction Background The use of Kriol inside and outside the Island. Statement of the problem General objective Specific objectives Rationale Theoretical Framework Bilingualism. Trilingualism.. Identity. Cultural Identity. Speech Community. Research Methodology Methods and techniques.. Interview.. Photographs.. Population and sampling. Data Analysis Conclusions Recommendations and Limitations References